Kesihatan mental dan tingkahlaku kewarganegaraan organisasi (TKO) dalam kalangan anggota polis semasa pandemik Covid-19 - Nor A’tikah Mat Ali,; Mohd Azrin Mohd Nasir,; Farah Nadia Mohd Faudzi,; Suzila Ismail,; Norzaliza Alis, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Mental health become an important contributor to enhance organizational citizenship behavior (OCB) among employee especially police officer in Malaysia. Good state of mental health dan implementation of OCB will enhance quality of work, personal performance, and productivity among police officer during pandemic Covid-19. This study focusses on identify the level of mental health from aspects of depression, anxiety and stress and the level of OCB that consist of behaviors directed towards the organizational (OCBO) and directed towards individuals (OCBI). The aim of this study also to the relationship between mental health and OCB among police officer in Malaysia. 615 police officers from Contingent Headquarters, Kuala Lumpur involved in this study. The finding revealed that mental health status among police officer in Malaysia is normal while the level of OCB is at an excessive stage. The result also proven the significant negative relationship between mental health and OCB. This study can be a guideline for Royal Malaysia Police (RMP) to emphasis on the important of mental health and promotion of OCB among police officer in Malaysia.